Anode co-valorization for scalable and sustainable electrolysis. Issue 20 (5th October 2021) - Jack, Joshua; Zhu, Wenjin; Avalos, José L.; Gong, Jinlong; Ren, Zhiyong Jason
Abstract : A state-of-the-art review on anode valorization reactions to improve the economic viability and scalability of water or CO2 electrolysis. Abstract : Increasingly abundant and low-cost renewable electricity is driving the fast development of electrolysis for energy storage and CO2 valorization. However, current electrolyzers rely on the oxygen evolution reaction (OER), which has been expensive, location limited, high-risk, and generates low value (O2 ) recovery. In this perspective review, we analyzed the state-of-the-art in electrolysis processes that use alternative anode reactions to improve the economic viability and scalability of water or CO2 electrolysis. We quantitatively compared a wide range of inorganic and organic electron donors in the anode that can lower energy costs and/or produce value-added products, and then assessed the use of different biotic and abiotic catalysts and the feasibility of using low-grade water sources as electrolytes. Through this wide-ranging assessment, we developed an example study for large-scale electrolysis in California, USA, provided long-term perspectives on OER substitutes for anode co-valorization, and delivered insight on future research directions.